Family environment and academic performance in students from the Language Center of the National University José María Arguedas – Andahuaylas 2018 - Aroquipa Durán, Yolanda (2019)
The research had as main purpose to determine the relationship between family environment and academic performance in the students of this study center, which was guided by the general hypothesis declaring that there is a direct and significant relationship between family environment and academic performance in students from the Language Center of the National University José María Arguedas de Andahuaylas in 2018. It is a basic research, descriptive level and non-experimental design of cross section, in which the scientific and statistical method has been used to achieve the expected results, the study considered a stratified sample of 90 students; amount determined by probabilistic sampling of a population of 117 students enrolled in the Language Center of the National University José María Arguedas at the basic and intermediate levels during the first academic semester of 2018. Concluding that with a level of significance of 5% it is affirmed that there is a direct and significant strong relationship between family environment and academic performance in students of the Language Center of the National University José María Arguedas of Andahuaylas, insomuch as that the correlation coefficient obtains a value of 0.778; establishing that, as much as better is the family environment, better will be the students' academic performance with respect to the English language.